Penggunaan Banten Daun Di Pura Dadia Alangkajeng Di Kelurahan Lelateng Kabupaten Jembrana (Kajian Nilai Pendidikan Agama Hindu) - Mardawa, I Made Dwi; Sudarsana, I Ketut; Wijaya Mahardika, I.G.N. Agung (Jurnal Penelitian Agama Hindu, 2019)
The phenomenon of religiousness in Bali shows the existence of various uniqueness and uniqueness itself. One form of uniqueness can be found on the use of leaf banten in Pura Dadia Alangkajeng, Apparently, this is related to the myth and role of leaf banten for klen Alangkajeng. This particularity is interesting to be studied more deeply so that the overall function and value in it becomes more clear. Problems raised in this study are: (1) Why is leaf banten used as a means of ceremony in Pura Dadia Alangkajeng ?; (2) What is the function of leaf banten in Pura Dadia Alangkajeng ?; (3) What is the value of Hindu religion education contained in the use of leaf banten in Pura Dadia Alangkajeng? This research is categorized into qualitative research using religious theory; the theory of structural functionalism; and constructivism theory. Qualitative data in this research is obtained by data collection method, consist of observation, interview, and document study which is processed by data analysis method with three stages: data reduction, data presentation and conclusion drawing.The leaf banten function for Alangkajeng clan is 1) the magical religious function of expressing the religious system (carrying out religious activities) and the conception of belief in God with all his manifestations; 2) social function, to strengthen the solidarity of family members of Dadia Alangkajeng; intensify the solidarity of family members; and show family identity; and 3) the function of education, to guide the Alangkajeng clan to behave in accordance with the conception of Tri Kaya Parisudha.The values ​​of Hindu religious education in the use of leaf banten in Pura Dadia Alangkajeng help clan members in the process of self evolution to a more perfect, noble, and happy stage. These values ​​are (1) the value of tattwe education, ie belief in the omnipotence of God (Bhattara Shiva) as the ultimate reality; (2) the value of ethical education that leads to the purification of mind (manacika parisuddha); sanctification of words (wacika parisuddha); and the sanctification of deeds (kayika parisuddha) and (3) the value of education of the event, marked by the presence of kuna drsta which underlies the execution of yadnya ceremony by using leaf banten; as well as piodalan ceremony in Pura Dadia conducted according to the time calculation in wariga system.